INFLUENCE OF INCOME FOR MUDHARABAH RESULTS AND MURABAHAH MARGIN INCOME ON PROFIT SHARIA BANK BUSINESS IN INDONESIA PERIOD 2015-2019 - Falahuddin F; Fuadi F; Muammar Khaddafi; Mohd. Heikal; Damanhur Abbas; Rico Nur Ilham (RADJA PUBLIKA, 2023)
This study aims to analyze the effect of mudharabah revenue sharing and murabahah margin income on operating profit of Islamic banks in Indonesia for the 2015 - 2019 period. The data used in this study are data published by Islamic banks in Indonesia using data from 2015 to 2019 and obtained sample data of 48 data. In selecting the sample, the researcher used a purposive sampling technique, which is a sample selection method based on certain criteria to obtain a representative sample of the population. The results of this study indicate that the revenue sharing of mudharabah and Murabahah Margin income has a positive and significant effect on Operating Profit at Islamic Banks in Indonesia for the 2015-2019 period.